From bench to bedside: Improving the clinical safety of GalNAc–siRNA conjugates using seed-pairing destabilization. Issue 12 (23rd June 2022) - Schlegel, Mark K; Janas, Maja M; Jiang, Yongfeng; Barry, Joseph D; Davis, Wendell; Agarwal, Saket; Berman, Daniel; Brown, Christopher R; Castoreno, Adam; LeBlanc, Sarah; Liebow, Abigail; Mayo, Tara; et al.
Abstract: Preclinical mechanistic studies have pointed towards RNA interference-mediated off-target effects as a major driver of hepatotoxicity for GalNAc–siRNA conjugates. Here, we demonstrate that a single glycol nucleic acid or 2′–5′-RNA modification can substantially reduce small interfering RNA (siRNA) seed-mediated binding to off-target transcripts while maintaining on-target activity. In siRNAs with established hepatotoxicity driven by off-target effects, these novel designs with seed-pairing destabilization, termed enhanced stabilization chemistry plus (ESC+), demonstrated a substantially improved therapeutic window in rats. In contrast, siRNAs thermally destabilized to a similar extent by the incorporation of multiple DNA nucleotides in the seed region showed little to no improvement in rat safety suggesting that factors in addition to global thermodynamics play a role in off-target mitigation. We utilized the ESC+ strategy to improve the safety of ALN-HBV, which exhibited dose-dependent, transient and asymptomatic alanine aminotransferase elevations in healthy volunteers. The redesigned ALN-HBV02 (VIR-2218) showed improved specificity with comparable on-target activity and the program was reintroduced into clinical development.